Literarhistorische Filmbiographien : Autorschaft und Literaturgeschichte im Kino : mit einer Filmographie 1909-2007 - Nierberle, Sigrid (Media and cultural memory ;, 2008)
The first biopics of poets were shown in cinemas in the USA in 1909 and in Germany in 1912. Since these early beginnings, a constant and rich tradition has developed of biopics of figures from literary history. This study is the first to carry out a longitudinal and lateral study of the genre. "Poet films" as they are called not only provide differing notions of authorship, but they also help write a history of literature as narrated in film. A filmography furnishes information on 180 feature films with themes from the history of the West European and US literary canons.